Capsaicin alleviates the hepatic clock gene disruption and gut microbiota dysbiosis in circadian rhythm disorder mouse model - Bolin Lin; Chi-Tang Ho; Yawen Wang; Jie Xiao; Muwen Lu (Food Science and Human Wellness)
As the body’s internal clock, the circadian rhythm regulates the energy expenditure, appetite, and sleep. There exists a close relationship between the host circadian rhythm and gut microbiota. In this work, a circadian disorder mouse model induced by constant darkness (CD) was constructed to investigate the regulating effects of capsaicin (CAP) on disturbances of metabolism homeostasis and gut microbiota in the respect of circadian rhythm-related mechanisms. Our results indicated that CAP reduced weight gain induced by circadian rhythm disorder in mice by inhibiting fat accumulation in liver and adipose tissue. The rhythmic expressions of circadian clock genes and lipid-metabolism related genes in liver were also recovered by CAP. Microbial study using 16S rRNA sequencing revealed that CAP modulated the gut microbiota richness, diversity and composition, and restored diurnal oscillations of gut microbes at the phylum and family level. These results indicated that CAP could alleviate CD-induced hepatic clock gene disruption and gut microbiota dysbiosis in mice, providing theoretical basis for CAP to be used as a muti-functional ingredient with great health-promoting effects.